Pāñcālī (pañcāyata) śāsana-paddhatiko aitihāsika vivecanā - Vajrācārya, Dhanavajra (Nepāla ra Eśiyālī Anusandhāna Kendra, Tribhuvana-Viśvavidyālaya, 1979)
Historical study on the panchayat system in Nepal.